2021
DOI: 10.1093/eurheartj/ehab128
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic therapy in diabetes: which, when, and for how long?

Abstract: Cardiovascular disease remains the main cause of mortality in individuals with diabetes mellitus (DM) and also results in significant morbidity. Premature and more aggressive atherosclerotic disease, coupled with an enhanced thrombotic environment, contributes to the high vascular risk in individuals with DM. This prothrombotic milieu is due to increased platelet activity together with impaired fibrinolysis secondary to quantitative and qualitative changes in coagulation factors. However, management strategies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 162 publications
(179 reference statements)
0
37
0
4
Order By: Relevance
“…Oral berberine (50 mg/kg/day) markedly improved insulin resistance, reduced the inflammation and JNK, IKK-β, and NF-κB p65 phosphorylation by inhibiting M1 macrophage activation in adipose tissue ( Ye et al, 2016 ). Owing to increased aldose reductase (AR) and NADPH oxidase (NOX) activities, platelet hyperreactivity and apoptosis during DM accounts for the accumulation of ROS ( Vara et al, 2019 ; Ajjan et al, 2021 ). It was demonstrated that 50 mM glucose induced platelet aggregation, apoptosis and superoxide production, which was neutralized by 25 and 50 μM berberine via inhibiting of AR, NOX and GSH reductase activities ( Paul et al, 2019 ).…”
Section: Effects Of Berberine On Vascular Diseasesmentioning
confidence: 99%
“…Oral berberine (50 mg/kg/day) markedly improved insulin resistance, reduced the inflammation and JNK, IKK-β, and NF-κB p65 phosphorylation by inhibiting M1 macrophage activation in adipose tissue ( Ye et al, 2016 ). Owing to increased aldose reductase (AR) and NADPH oxidase (NOX) activities, platelet hyperreactivity and apoptosis during DM accounts for the accumulation of ROS ( Vara et al, 2019 ; Ajjan et al, 2021 ). It was demonstrated that 50 mM glucose induced platelet aggregation, apoptosis and superoxide production, which was neutralized by 25 and 50 μM berberine via inhibiting of AR, NOX and GSH reductase activities ( Paul et al, 2019 ).…”
Section: Effects Of Berberine On Vascular Diseasesmentioning
confidence: 99%
“…Diabetes patients have a prothrombotic condition and are at a greater risk of cardiovascular events than individuals who do not have diabetes 149 . Antithrombotic or antiplatelet treatments may be linked with a greater absolute decrease in recurrent episodes in diabetes in comparison to those without diabetes 105,106 . For primary prevention of CVD in diabetes, antiplatelet therapy (aspirin; 75–100 mg daily) is indicated in patients with 10‐year cardiovascular risk greater than 10% in those aged ≥50 years without a high risk of bleeding.…”
Section: Resultsmentioning
confidence: 99%
“…149 Antithrombotic or antiplatelet treatments may be linked with a greater absolute decrease in recurrent episodes in diabetes in comparison to those without diabetes. 105,106 For primary prevention of CVD in diabetes, antiplatelet therapy (aspirin; 75-100 mg daily) is indicated in patients with 10-year cardiovascular risk greater than 10% in those aged ≥50 years without a high risk of bleeding. A 2019 meta-analysis by Seidu et al demonstrated a significant reduction in stroke with a low-dosage (≤100 mg/day) of aspirin dosage in diabetes patients (RR 0.75, 95% CI 0.59-0.95).…”
Section: Antiplatelet Therapies In Diabetes For Primary and Secondary...mentioning
confidence: 99%
“…Second, the elderly are often accompanied by various comorbidities so that receiving large amounts of drugs will increase the risk of interactions with the antithrombotic drugs given. Therefore, therapy monitoring must be carried out more carefully on the dose, drug effects, or side effects of drugs [17] , [18] .…”
Section: Discussionmentioning
confidence: 99%